Impacts on Poverty of Removing Fuel Import Subsidies in Nigeria - Siddig, Khalid; Minor, Peter; Grethe, Harald; Aguiar, Angel; Walmsley, Terrie (World Bank, Washington, DC, 2015)
The petroleum sector contributes substantially to the Nigerian economy; however, the potential benefits are diminished because of the existence of significant subsidies on imports of petroleum products. Subsidies on imported petroleum products are considered to be an important instrument for keeping fuel prices, and hence the cost of living, low. The costs of these subsidies, however, have risen dramatically in recent years along with increased volatility in world petroleum and petroleum product prices and increased illegal exportation of subsidized petroleum products into neighboring countries. Removing the subsidy on fuel is one of the most contentious socioeconomic policy issues in Nigeria today. In this paper, an economy-wide framework is used to identify the impact of removing the fuel subsidy on the Nigerian economy and investigate how alternative policies might be used to meet socioeconomic objectives related to fuel subsidies. The results show that although a reduction in the subsidy generally results in an increase in Nigeria’s gross domestic product, it can have a detrimental impact on household income, and in particular on poor households. Accompanying the subsidy reduction with income transfers aimed at poor households or domestic production of petroleum products can alleviate the negative impacts on household income.